Numerical simulation study on the effects of liquid water atomization on the flow field and performance of aluminum-based water ramjet engines - Zhang, Yuntian; Wu, Yunkai; Cao, Xiwei; Liu, Yuanshu; Sun, Yongqiang; Yang, Jing; Junli, Liu (Frontiers in Mechanical Engineering, 2023)
In order to investigate the effects of different water inlet droplet diameters on the performance of aluminum-based water ramjet engines, the internal flow field of the engine was analyzed through numerical simulation. The results showed that by selecting a suitable water droplet diameter at the water inlet and controlling the time required for water droplet evaporation and heat absorption, the working range of aluminum-water combustion reaction can be expanded and the specific impulse of the engine can be increased. In engine design and practical application, the design of the water injection nozzle upstream of the engine is critical, and the droplet diameter at the water inlet should be controlled within a suitable range. A diameter that is too large will reduce the evaporation efficiency and hinder the further diffusion of combustion reaction. Droplet sizes that are too small will rapidly evaporate, causing the temperature in the flow field to decrease rapidly, leading to a large range of low-temperature regions in the main reaction zone of the combustion chamber, thereby reducing the overall aluminum-water reaction rate of the engine. In addition, the variation of droplet diameter in the downstream water atomization nozzle has little effect on the aluminum-water reaction in the main combustion zone. However, reducing the droplet diameter can facilitate the downstream diffusion of the combustion reaction, further expanding the combustion range and increasing the specific impulse. Furthermore, it can also reduce the temperature near the wall, which is beneficial for reducing the overall thermal protection requirements of the engine.